Technology and innovation report, 2018 harnessing frontier technologies for sustainable development (United Nations, 2018)
"The Technology and Innovation Report 2018: Harnessing Frontier Technologies for Sustainable Development notes that change is becoming exponential thanks to the power of digital platforms and innovative combinations of different technologies that become possible every day. This opens exciting possibilities for the democratization of frontier technologies to materialize in development solutions. The Report proposes strategies and actions, some of them based on existing experiences in STI policy for development, and some more innovative ones to make technology an effective means of implementation of our common development agenda -nationally and globally. The Report also suggests that countries develop policies to help people navigate the transition period that lies ahead. This may require that stakeholders adapt the social contract to the new world that frontier technologies are forming. ... Most crucially,there is an urgent need for a sustained effort by the international community to ensure that the multiple gaps in technological capabilities that separate developed and developing countries are closed. Investment in hard and soft infrastructure and human capital, complemented by a scaled up, coherent and accelerated effort to enhance innovation systems for sustainable development are necessary to spread the economic, social and environmental benefits of frontier technologies. By providing a platform for policy dialogue and experience-sharing, and through our capacity-building programmes, UNCTAD and the UN Commission for Science and Technology for Development,which we service, have an international policy role to fulfil in the development of the global response to those challenges. Our intention is that the Technology and Innovation Report 2018 will help launch a dialogue about how to harness technology for the achievement of the SDGs and in larger and more profound sense, the shared future of the people of the world." -- Publisher's website.